2014
DOI: 10.5194/nhess-14-705-2014
|View full text |Cite
|
Sign up to set email alerts
|

Modulational instability and wave amplification in finite water depth

Abstract: Abstract. The modulational instability of a uniform wave train to side band perturbations is one of the most plausible mechanisms for the generation of rogue waves in deep water. In a condition of finite water depth, however, the interaction with the sea floor generates a wave-induced current that subtracts energy from the wave field and consequently attenuates the instability mechanism. As a result, a plane wave remains stable under the influence of collinear side bands for relative depths kh ≤ 1.36 (where k … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 49 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…By contrast, field data from Lake George, Australia included in the same study indicate notable amplifications beyond the second-order crest height statistics in the steepest sea states. Additionally, experimental and numerical studies [38,39] of idealized wave groups have shown that instabilities can develop due to oblique perturbations; the theoretical basis having been provided by Hayes [40]. These latter results are important, not least because the analysis of field data from intermediate water depths has confirmed the existence of both unexepectedly large wave crests [41,42] and crest height distributions departing from second-order theory [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, field data from Lake George, Australia included in the same study indicate notable amplifications beyond the second-order crest height statistics in the steepest sea states. Additionally, experimental and numerical studies [38,39] of idealized wave groups have shown that instabilities can develop due to oblique perturbations; the theoretical basis having been provided by Hayes [40]. These latter results are important, not least because the analysis of field data from intermediate water depths has confirmed the existence of both unexepectedly large wave crests [41,42] and crest height distributions departing from second-order theory [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In this section, the High-Order Spectral method used in HOS-ocean code is presented. HOS models have been widely used for the study of wave propagation in open domains starting from the original work of [31] & [8] up to the analysis of complex wave phenomena [27,28,29,16], including freak waves [12,32,24], among others. Extensions of the original HOS model to include wind forcing effects [30,19] and jet current effects [25] are also worth to mention.…”
Section: High-order Spectral Methodsmentioning
confidence: 99%
“…HOS models have been widely used and validated by several authors to study different physical mechanisms: e.g. in recent years nonlinear energy transfers [27], modulational instabilities [16], [28], bi-modal seas [29], freak waves [12,32,24] . .…”
Section: Introductionmentioning
confidence: 99%
“…HOS models have been widely used for the study of wave propagation in open domains starting from the original work of [42] & [13] up to the analysis of complex wave phenomena [35,38,39,19], including freak waves [15,43].…”
Section: Hos-oceanmentioning
confidence: 99%
“…Several physical phenomena have been studied thanks to this highly nonlinear model, e.g. non-linear energy transfers [35], modulational instabilities [19,38], and bi-modal seas [39] among others.…”
Section: Introductionmentioning
confidence: 99%